One-year outcomes of a surgical technique for stabilizing the intraocular lens–capsular bag complex in severely subluxated cataracts using permanent polypropylene capsular hooks - Feng, Rui; Li, Guoliang; Luo, Yanni; Wang, Binjian; Zhao, Yihao; Qu, Chao (Frontiers in Medicine, 2025)
PurposeTo report the one-year follow-up outcomes of a surgical technique designed to rescue severely subluxated cataracts and stabilize the intraocular lens (IOL)–capsular bag complex using permanent polypropylene capsular hooks.MethodsFour patients (four eyes) with severely subluxated cataracts underwent surgery. A spatula was used to elevate and stabilize the dislocated lens in the retropupillary space to facilitate capsulorhexis. Phacoemulsification and aspiration were performed using capsular retractors and a capsular tension ring. Permanent polypropylene capsular hooks were implanted to stabilize the IOL–capsular bag complex. Postoperative outcomes were assessed over a follow-up period of at least 1 year. Descriptive analyses were performed to summarize and report the outcomes of this limited case series.ResultsThe follow-up period ranged from 13 to 20 months. All patients demonstrated improved and stable subjective refraction and best-corrected visual acuity (BCVA). At the final follow-up, the mean postoperative prediction error was −0.17 ± 0.29 D. Slit-lamp examinations showed that the IOL–capsular bag complex and the permanent polypropylene capsular hooks remained stable. Anterior segment optical coherence tomography (AS-OCT) revealed minimal IOL tilt of 1.52 ± 1.20. No intraoperative or postoperative complications were reported.ConclusionThe technique offers a viable approach for managing severely subluxated cataracts, providing stable support for the IOL–capsular bag complex and yielding favorable clinical outcomes. However, as this novel technique was evaluated in a small sample size, further studies with larger cohorts and longer follow-up periods are needed to confirm its long-term safety and efficacy.